(untitled) (Research, Society and Development, 2020)
Combined hormonal contraceptives (CHC) are used among women of the wordwide, increasing the risk of venous thromboembolism (VTE) including deep vein thrombosis (DVT) and pulmonary embolism (PE). The objective was to identify studs with thrombotic effects in women of child-bearing age associated with the use of combined oral contraceptives. The methodology used was an integrative review of the PubMed database articles using the health descriptors: “combined oral contraceptives”, “thrombotic effects”, “blood clot”, and Portuguese version. The result found in the article showed that the continuous and prolonged use of CHC increase the risk of platelet aggregation and low thrombolysis favoring the formation of thrombi, resulting in accentuated DVT developtment. Thus, it is important to observe the medical eligibility criteria to define use of CHC for patients taking into account the risks a thrombotic disorder.